Modern environmental problems of the Kyzylorda region: challenges and possible solutions - Alimbaev, T.; Mazhitova, Zh.; Bogenbayeva, A.; Omarova, B. (Ecological and biological well-being of flora and fauna (EBWFF-2020), 2020)
This paper examines the environmental problems of the Kyzylorda region associated with the industrial enterprises’ activities in the region. The article notes along with economic growth in the mining industry, which is one of the main sectors of the regional economy, the level of pollution in the surrounding ecosystem is increasing. On the one hand, the authors are convinced the growth of the economic potential in the mining industry, space activities and the transition to market mechanisms for the economy development have generated a major growth in the potential of the region turning it into one of the largest developed regions of the Republic of Kazakhstan. On the other hand, an increase in industrial production without taking into account the ecological characteristics of the region with an increase in deformations of sectoral proportions and socio-economic structure, anthropogenic impact on the environment gave rise to a crisis in the regional ecology. According to the authors, reducing the harmful impact of the Baikonur complex on the environment, preserving the Aral ecosystem, competently using the historical experience of irrigated agriculture, as well as work in the field of environmental awareness and education of nature users will create a favourable environment for a significant improvement in the environmental situation in the region.